(3fbO GdQLGds - (3GdJaQjTj , eUWaj Hf GdMSjf GdMSjfj,J (B1030 (3g` s
(3ChdgG (B:s
(3WQjb GdTjN Edi CHj WGdH GdCfHGQi hZjQg, hajg CMeO Hf YHOhf s
(3BNQgG (B:s
(3hHgPG GdESfGO Yf GdTjNjf dCLdjf GdTjN aNQ GOjf hGdSjO YejO GdOjf hGdMeO ddg hMOg s
(3fSNI KGfjIs
(3oedMb HgG HYV hQbGJ aj GdhVGYjfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B232 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B247s
Keywords: (3GdJGQjNs